GALLSTONE ILEUS WITH CHOLECYSTO-DUODENAL FISTULA IN AN ELDERLY MALE - Umer, Said; Butt, Usman Ismat; Toor, Asad Ali; Razzaq, Zeeshan; Farooka, Muhammad Waris; Noreen, Shazia; Butt, Abeeda; Redmond, Henry Paul (Journal of Ayub Medical College Abbottabad, 2018)
Gall stone ileus associated with cholecysto-duodenal fistula is a rare pathology. It most commonly presents in elderly females in 72-90% of cases. In such a case, a patient typically presents with recurrent attacks of sub-acute intestinal obstruction which usually resolves completely with conservative management only to recur again after some time. We are reporting a case of an 85-year-old gentleman who presented to us with gallstone ileus associated with cholecysto-duodenal fistula and his subsequent management. He underwent Laparotomy with enterotomy, stone extraction, Cholecystectomy and Graham's patch repair of the fistula. The purpose of this case report is to discuss a rare case of gall stone ileus associated with cholecysto-duodenal fistula. The diagnosis was confirmed using imaging and appropriate and timely surgical intervention for both mechanical intestinal obstruction and the fistula was undertaken. Keywords: Gallstone ileus; Pneumo-bilia; Abdominal X-ray